A.G. Davis, Charter and Ordinances, and Rules and Orders of the City Council 52 (1874) - (:unkn) unknown (My University, 1874)
§ 4: No person shall haul unto, or lay at any wharf in the city, any vessel having on board more than twenty-five pounds of gun-powder, nor discharge or receive on board exceeding that quantity, without having first obtained from the Mayor a permit therefor, designating the wharf at which said powder may be landed or received on board.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER